2012
DOI: 10.3945/ajcn.112.037770
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of saturated fat by food source and incident cardiovascular disease: the Multi-Ethnic Study of Atherosclerosis

Abstract: Associations of SF with health may depend on food-specific fatty acids or other nutrient constituents in foods that contain SF, in addition to SF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
4
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(239 citation statements)
references
References 42 publications
5
204
4
8
Order By: Relevance
“…5 Esta relación ha sido confirmada por estudios recientes que señalan que el consumo de productos lácteos está inversamente asociado con enfermedades cardiovasculares y posiblemente también con el incremento del IMC. 31 Es necesario destacar que la presente investigación sólo estudió la relación entre el IMC y el consumo de lácteos con azúcar añadida por lo que, si se analizaran lácteos más saludables que no contuvieran hidratos de carbono añadidos como azúcar, chocolate u otros, la relación podría aumentar.…”
Section: 29unclassified
“…5 Esta relación ha sido confirmada por estudios recientes que señalan que el consumo de productos lácteos está inversamente asociado con enfermedades cardiovasculares y posiblemente también con el incremento del IMC. 31 Es necesario destacar que la presente investigación sólo estudió la relación entre el IMC y el consumo de lácteos con azúcar añadida por lo que, si se analizaran lácteos más saludables que no contuvieran hidratos de carbono añadidos como azúcar, chocolate u otros, la relación podría aumentar.…”
Section: 29unclassified
“…However, the majority of studies in recent years suggest no adverse effects on surrogate markers of cardiovascular disease (CVD) or cardiovascular prognosis [18,32]. The milk and dairy products used in those studies are mostly from cow and have a lower fat content than those from ewe’s milk, and their lipid profile is different.…”
Section: Introductionmentioning
confidence: 99%
“…A lower hazard ratio (HR) for CVD was reported for every 5 g/d (HR 0·79; 95 % CI 0·68, 0·92) or 5 % of energy from dairy SFA (HR 0·62; 95 % CI 0·47, 0·82), whereas the equivalent intake of SFA from meat sources was associated with greater HR for CVD (HR for +5 g/d and a +5 % of energy from meat sources of SFA: 1·26; 95 % CI 1·02, 1·54 and 1·48; 95 % CI 0·98, 2·23, respectively) (13) . Furthermore, the substitution of 2 % of energy from meat sources of SFA with energy from dairy SFA was associated with a 25 % lower CVD risk (HR 0·75; 95 % CI 0·63, 0·91), suggesting that dairy foods containing SFA attenuated the detrimental association of SFA with CVD mortality.…”
Section: )mentioning
confidence: 99%
“…This can give rise to disparity between the biological effects of nutrients in different foods that may have contributed to the inconsistencies in the relationships of different SFA-rich foods and CVD mortality. Clear evidence for this comes from the Multi Ethnic Study of Atherosclerosis, in which different SFA-rich foods were shown to produce differential effects on CVD risk (13) . In 5209 subjects after a 10-year period (from 2000 to …”
Section: Saturated Fat From Milk and Cvdmentioning
confidence: 99%